Is Enhanced External Counterpulsation (EECP) A- Last Resort Treatment of Refractory Angina? - Siddique, Md Abu (University Heart Journal, 2009)
doi: 10.3329/uhj.v5i1.3431 University Heart Journal Vol. 5, No. 1, January 2009 1-2